1999
DOI: 10.1002/1529-0131(199908)42:8<1644::aid-anr12>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2 balance of peripheral T helper cells in systemic lupus erythematosus

Abstract: Objective. To analyze the Th1/Th2 balance of peripheral Th cells in patients with systemic lupus erythematosus (SLE).Methods. The Th1:Th2 ratio was analyzed in 3 groups: SLE without proteinuria (group I; n ‫؍‬ 23), SLE with proteinuria (group II; n ‫؍‬ 31), and normal controls (group III; n ‫؍‬ 24). Group II patients who had undergone renal biopsy were classified into 3 subgroups based on their renal histopathologic findings. The intracellular cytokine detection method with flow cytometry was used to quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
153
3
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(167 citation statements)
references
References 34 publications
10
153
3
1
Order By: Relevance
“…Especially, those findings may point to the strong fidelity lineage of Th17 in active disease SLE or even a terminal differentiation stage related with a repeated antigen challenge as compared to inactive SLE or normal control groups. Furthermore, consistent with other human studies [31,32] that have demonstrated a lower number of Th1 cells in active SLE patients, our data suggest that the cytokine profile of Th17 cells may be essential for synergistically induced Th1-type cytokines and also potentially be distinct according to the pro-inflammatory environment. Thus, the local cytokine milieu may induce new transcription factors and modify cytokine production even in fully polarized effector T-cell lineages.…”
Section: Discussionsupporting
confidence: 91%
“…Especially, those findings may point to the strong fidelity lineage of Th17 in active disease SLE or even a terminal differentiation stage related with a repeated antigen challenge as compared to inactive SLE or normal control groups. Furthermore, consistent with other human studies [31,32] that have demonstrated a lower number of Th1 cells in active SLE patients, our data suggest that the cytokine profile of Th17 cells may be essential for synergistically induced Th1-type cytokines and also potentially be distinct according to the pro-inflammatory environment. Thus, the local cytokine milieu may induce new transcription factors and modify cytokine production even in fully polarized effector T-cell lineages.…”
Section: Discussionsupporting
confidence: 91%
“…This variation may also alter the receptor function because the Met14 variant shows a decreased response to IFN compared to Val14 variant [14], and because IFN induces a differentiation of Th0 cells to Th1 cells, will decreased effect of IFN shift the Th1/Th2 balance towards Th2. As mentioned before, shift toward Th2 is a major feature of SLE [58].…”
Section: Ifn Receptormentioning
confidence: 61%
“…Increased IFN-␥ mRNA and decreased IL-4 gene expression are found in PBMCs taken from SLE patients (5). Th1 cytokines, including IFN-␥, are present in tissue of SLE patients with the most severe disease, with enhanced production of this cytokine by peripheral blood cells and in the kidneys of patients with severe lupus glomerulonephritis, compared with individuals with milder renal disease (6,7). Likewise, in mice with lupus, Th1 cytokines play a dominant role in disease pathogenesis (8).…”
Section: Il-10 Regulates Murine Lupusmentioning
confidence: 99%